The harvestman genus Taracus Simon 1879, and the new genus Oskoron (Opiliones: Ischyropsalidoidea: Taracidae) - Shear, William A.; Warfel, Joseph G. (Zootaxa, 2016)
The ischyropsalidoid genus Taracus Simon 1879 is reviewed and all previously named species are redescribed. Taracus nigripes Goodnight & Goodnight, 1943 is synonymized with T. packardi Simon 1879, and T. malkini Goodnight & Goodnight 1945 with Oskoron spinosus (Banks) 1894; the type locality of T. gertschi Goodnight & Goodnight 1942 is corrected from “eastern Oregon” to Rose Lake, Idaho, based on original labelling. The following new species of Taracus are described: T. carmanah (Vancouver Island), T. marchingtoni (Oregon), T. taylori, T. spesavius (both Nevada), T. timpanogos (Utah), T. audisioae, T. ubicki, and T. fluvipileus (all California). A new genus Oskoron is based upon O. spinosus (Banks) 1894, originally described in Taracus, and also includes two new species, O. brevichelis (Oregon, Washington) and O. crawfordi (Washington). New locality records extend the known distribution of Taracus to the Canadian provinces of Alberta and British Columbia and the US states of Montana, Wyoming, Utah, Nevada and New Mexico. Schönhofer’s (2013) proposal of a family Taracidae for Taracus, Hesperonemastoma Gruber 1970 and Crosbycus Roewer 1914 is discussed.